Exploring biodegradative efficiency: a systematic review on the main microplastic-degrading bacteria - da Silva, Milena Roberta Freire; Souza, Karolayne Silva; Motteran, Fabricio; de Araújo, Lívia Caroline Alexandre; Singh, Rishikesh; Bhadouria, Rahul; de Oliveira, Maria Betânia Melo (Frontiers in Microbiology, 2024)
Microplastics (MPs) are widely distributed in the environment, causing damage to biota and human health. Due to their physicochemical characteristics, they become resistant particles to environmental degradation, leading to their accumulation in large quantities in the terrestrial ecosystem. Thus, there is an urgent need for measures to mitigate such pollution, with biological degradation being a viable alternative, where bacteria play a crucial role, demonstrating high efficiency in degrading various types of MPs. Therefore, the study aimed to identify bacteria with the potential for MP biodegradation and the enzymes produced during the process. The meth-odology used followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol. The research yielded 68 eligible studies, highlighting bacteria from the genera Bacillus, Pseudomonas, Stenotrophomonas, and Rhodococcus as the main organisms involved in MP biodegradation. Additionally, enzymes such as hydrolases and alkane hydroxylases were emphasized for their involvement in this process. Thus, the potential of bacterial biodegradation is emphasized as a promising pathway to mitigate the environmental impact of MPs, highlighting the relevance of identifying bacteria with biotechnological potential for large-scale applications in reducing MP pollution.